2017
DOI: 10.1093/hmg/ddx046
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting sphingosine kinase 2 mitigates mutant Huntingtin-induced neurodegeneration in neuron models of Huntington disease

Abstract: Huntington disease (HD) is the most common inherited neurodegenerative disorder. It has no cure. The protein huntingtin causes HD, and mutations to it confer toxic functions to the protein that lead to neurodegeneration. Thus, identifying modifiers of mutant huntingtin-mediated neurotoxicity might be a therapeutic strategy for HD. Sphingosine kinases 1 (SK1) and 2 (SK2) synthesize sphingosine-1-phosphate (S1P), a bioactive lipid messenger critically involved in many vital cellular processes, such as cell survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 76 publications
5
32
0
Order By: Relevance
“…Furthermore, ongoing clinical trials with SK2 inhibitors have not reported any drug-related toxicities in humans [ 11 ], including neurotoxicity which is a common side-effect of bortezomib [ 49 ]. Indeed, in some contexts SK2 inhibition appears neuroprotective [ 50 ]. Thus, combining SK2 inhibitors with bortezomib appears feasible in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ongoing clinical trials with SK2 inhibitors have not reported any drug-related toxicities in humans [ 11 ], including neurotoxicity which is a common side-effect of bortezomib [ 49 ]. Indeed, in some contexts SK2 inhibition appears neuroprotective [ 50 ]. Thus, combining SK2 inhibitors with bortezomib appears feasible in humans.…”
Section: Discussionmentioning
confidence: 99%
“…SPHK2 has been found to participate in repressor complexes with histone deacetylases (HDAC1 and 2), while S1P can bind both HDAC proteins and inhibit their deacetylase activity [ 59 ]. These varied mechanisms of nuclear signaling appear to be important for inflammaging and neurodegenerative conditions (Alzheimer’s disease (AD)), along with the above mentioned sphingolipid-mediated modulation of transcription factors [ 49 , 60 , 61 ].…”
Section: Sphingolipid Biosynthesis and Signalingmentioning
confidence: 99%
“…In neurons, SPK2 could be expressed in the cytoplasm, mitochondria and nucleus under physiological or pathological conditions. 41 , 42 , 43 , 44 Our previous finding showed that preconditioning mainly upregulates endogenous SPK2 in the cytoplasm. On the other hand, apoptosis-stimulating protein of p53-2 (ASPP2) could bind to Bcl-2 in the nucleus to prevent its translocation to the cytoplasm, thus contributing to Beclin-1-initiated autophagy.…”
Section: Resultsmentioning
confidence: 95%
“… 58 , 60 , 63 , 64 , 65 In neurons, SPK2 can be expressed in the cytoplasm, mitochondria and nucleus under physiological or pathological conditions. 41 , 42 , 43 , 44 Recent study suggest that overexpressed SPK2 in nucleus is neurotoxic and promotes DNA double-strand breaks in cultured primary neurons. 44 However, our data showed that SPK2 was overexpressed in both the cytoplasm and nuclei of the SPK2 overexpressed neurons and HT22 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation